O programa sala de leitura e seus reflexos nas histórias de leitura de alunos e professores de uma escola estadual paulista - Gimenez, Queila Silva [UNESP] (2015)
This paper is an investigation about the relations between the Room to Read Project, introduced by the state government in a state school in the countryside of the state of São Paulo in 2009, and the reading background of the teachers responsible for the Room as a reading mediator, and the reading background of three students chosen by those teachers due to the frequency they attend this Room. By analyzing qualitative data, we tried to understand how the Room to Read works, and the profile of this school community was studied considering the formation of its cultural identity and relating it with the reading as a cultural product. In order to carry out this investigation, interactions were made by means of interviews recorded with the teachers responsible for the Room to Read and with the chosen students. The interviews were analyzed, qualitatively investigating the participant's reading stories and experiences, and based on the theoretical and methodological approaches of Clandinin and Connelly's (2011) narrative research. In order to understand what those Canadian authors refer to, we relied on Gadamer's (1997) philosophical hermeneutics, trying to analyze how much of those reading experiences can be (or cannot be) related to the frequency the students go to Room to Read during the daily school routine and how those experiences help (or do not help) their identity formation within the school. We also relied on Soares's (2006; 2010) and Kleiman's (2010) studies on literacy, on anthropologist Michèle Petit's (2008; 2010) records about reading experiences, and on Roger Chartier's (1996; 1999) contributions related to reading, books and cultural practices, which are in line with Lipovetsky and Serroy's (2011) world-culture approach. Regarding identity formation and its relation with the reading role, we relied on Bauman's (2005) e Hall's (2011; 2013) work concerning identity...